Unsteady Transonic Cascade with a Subsonic Leading-Edge Locus - Shivamoggi, B.K. (Engineering Transactions, 1983)
This paper devises an inviscid, linearised analySis of an unsteady transonic cascade with a subsonic leading-edge locus. First, the flow in the pre-interference zone (the one upstream of the cascade) is determined. This is then used as an initial value to determine the flow in the region between the blades downstream of the pre-interference zone. In deriving the solution for the pre-interference zone, the problem is first cast as an initial-value problem. The periodicity requirement due to the cascade arrangement enables one to eliminate the unknown initial conditions and thus lead to the integral equations for the velocity potentials. The integral equations are solved by successive approximations.